Pengembangan Model Kewirausahaan Berbasis Teknologi (Technopreneurship) Di Era Bisnis Online - Amaluddin Tanjung; Irma Tussa’diyah Hasibuan; Nur Khotima; Suwandi Suwandi (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
In the era of online business that continues to grow, the development of technology-based entrepreneurial models, or technopreneurship, has become the main focus of attention. Rapid changes in information technology and the internet have changed the way we do business. This article will discuss how technopreneurship has become the key to exploiting new opportunities in the digital world. In this discussion, we will explain the importance of technopreneurship in the context of online business, including the role of technological innovation, use of online platforms, e-commerce, and mobile applications. This research uses library research, namely a method of collecting data by understanding and studying theories from various literature related to the research. This data collection uses the method of searching for sources and constructing them from various sources, for example books, journals and research that has already been carried out. Library materials obtained from various references are analyzed critically and must be in-depth in order to support the propositions and ideas.